2013
DOI: 10.1080/0158037x.2012.684375
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in collaborative research communities: a multicultural, multidisciplinary thesis writing group in public health

Abstract: Writing groups for doctoral students are generally agreed to provide valuable learning spaces for PhD candidates. Here an academic developer and the seven members of a writing group formed in a Discipline of Public Health provide an account of their experiences of collaborating in a multicultural, multidisciplinary thesis writing group. We consider the benefits of belonging to such a group for PhD students who are operating in a research climate in which disciplinary boundaries are blurring and where an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 44 publications
(54 reference statements)
3
28
0
1
Order By: Relevance
“…In one example, an expert-led group transitioned into a peer-to-peer group as the academic facilitator gradually stepped aside leaving the group to conduct itself as a peer-to-peer writing group (Guerin et al, 2013). Another example shows efforts to equalise expertise across the group, with academic staff and postgraduates using day-long writing retreats at each other's homes or evening meetings in their institution's library to develop and maintain their practices.…”
Section: Expertisementioning
confidence: 97%
“…In one example, an expert-led group transitioned into a peer-to-peer group as the academic facilitator gradually stepped aside leaving the group to conduct itself as a peer-to-peer writing group (Guerin et al, 2013). Another example shows efforts to equalise expertise across the group, with academic staff and postgraduates using day-long writing retreats at each other's homes or evening meetings in their institution's library to develop and maintain their practices.…”
Section: Expertisementioning
confidence: 97%
“…Social in nature, such groups provide context to inform the practice of writing and student mentoring by faculty and peers. When successful, the benefits of participating in writing groups are numerous: writing groups can serve as supportive communities, encourage daily writing practices, improve language and writing skills, facilitate new insights, and bolster the confidence and writing self-efficacy of participants (Aitchison, 2009;Cuthbert and Spark, 2008;Guerin et al, 2013;Larcombe et al, 2007;Maher et al, 2008). Writing groups constitute a promising strategy to facilitate meaningful student engagement and socialization surrounding the social practice of writing in interdisciplinary programs.…”
Section: Writing Groupsmentioning
confidence: 99%
“…Writing groups constitute a promising strategy to facilitate meaningful student engagement and socialization surrounding the social practice of writing in interdisciplinary programs. Previous studies of multi-disciplinary writing groups have found them to be a beneficial forum, for example, encouraging graduate students to develop a sense of professional identity by serving as proponents for their respective disciplines, (Cuthbert et al, 2009) and pushing students to practice communicating ideas to academically-diverse audiences (Guerin et al, 2013). To date, however, there is a paucity of literature that specifically addresses writing groups in interdisciplinary doctoral programs and how they may support student learning.…”
Section: Writing Groupsmentioning
confidence: 99%
“…Diversity in the group can support the acceptance of a variety of views on a person's work and can also help students develop awareness of the variety of audiences who might encounter their writing (Ferguson, 2009;Guerin et al, 2013). Multidisciplinary groups can add to discipline-based doctoral education by providing breadth in students' development; in this sense it complements rather than compromises disciplinary education (Cuthbert, Spark, & Burke, 2009).…”
Section: The Case For Generic Writing Advicementioning
confidence: 99%